Redistribution of B-10 absorbed by leaves and roots of cashew seedlings - Faria Simao Canesin, Regina Celia [UNESP]; Buzetti, Salatier [UNESP]; Souza, Juliana Aparecida de [UNESP] (Taylor & Francis Inc, 2015)
Boron (B) is transported mainly in the xylem, but by using isotopic tracers it was possible to verify that B has significant mobility in the phloem of polyols-producing species. Thus, the objective of this study was to evaluate the mobility of B-10 applied to cashew plants. The experiment was conducted from 05/10 to 07/10/2010 in a greenhouse of University of Sao Paulo State-UNESP, Ilha Solteira Campus, State of Sao Paulo, Brazil. 0.5 mg of B L-1 of soil was used in the substrate. A solution of 255 mg of B L-1 was used in recently mature and fully developed leaves. The total content of B and and percentage of boron in the plant derived from fertilizer (Bppf%) were evaluated in the old and new leaves stemming at 30 and 60 days after the application of B-10. As evidenced, B applied to leaves had restricted mobility in cashew tree. However, B applied in the substrate was absorbed and translocated to young leaves.
Keywords: Boron; Micronutrient; Mobility